The Effect of Spiritual Practice along with Routine Medical Care on the Recovery of Patients Hospitalized with Covid-19: a Randomized Clinical Trial - A. Jahangir; B. Mousavi; R. Mahdavi; M. Asgari; M. Karbakhsh (Afarand Scholarly Publishing Institute, 2020)
Aims: This study was conducted to determine the effects of spiritual practice along routine medical care on the recovery of patients admitted with Covid-19. Materials & Methods: In a single-blinded clinical trial study 64 hospitalized patients with Covid-19, were randomly assigned in to two groups of intervention (spiritual practice+ routine treatment) and comparison (routine treatment). The intervention was performed using religious teachings, spiritual practice was taught to the patients in the intervention group with the intention of recovery and comfort. Spiritual practice was reciting Surah "Al-Hamd" and "Ya-Allah". The intervention group accomplished spiritual practice three times a day (21 times in total) for 7 days. Information gathered on demographic characteristics, depression and anxiety score, length of hospital stay, ICU transfer, intubation, and patient death. The Hospital Anxiety and Depression Scale (HADS) questionnaire was used to determine the symptoms of depression and anxiety. Findings: A total of 35 participants in the comparison group and 29 in the intervention group completed the study. After intervention, there was no significant difference between the length of hospitalization days between the intervention group (5.8±1.7) and the comparison (6.7±1.7). The rate of ICU request was significantly higher in the comparison group (40%,n=14) than in the intervention group (3.4%, n=1) (P <0.001). In the intervention group, no cases of intubation and death occurred, in the comparison group, these rates were 40% (n=14) and 45.7% (n=16), respectively, and the difference was significant (P <0.001). The mean difference of anxiety score before and after spiritual practice in the intervention group was 3.1 (±3.6) and the comparison was 0.9 (±2.6) (P = 0.03). The mean difference of depression in the intervention group was 1.5 (2.1) and the comparison was 0.9 (1.8) (P <0.001). Conclusion: Spiritual practice along with routine medical care, can leadto less mortality, ICU transmission, intubation, improved anxiety/depression, as well as, improved recovery among Covid-19 hospitalized patients.